Paradise Laborers Hotel Work in the Global Economy - Adler, Patricia A.; Adler, Peter (Cornell University Press, 2018)
Resorts have become important to American society and its economy; one in eight Americans is now employed by the tourism industry. Yet despite the ubiquity of hotels, little has been written about those who labor there. Drawing on eight years of participant observation and in-depth interviews, the renowned ethnographers Patricia A. Adler and Peter Adler reveal the occupational culture and lifestyles of workers at five luxury Hawaiian resorts.These resorts employ a workforce that is diverse in gender, class, ethnicity, and nationality. Hawaiian resort workers, like those in nearly all resorts, consist of four groups. New immigrants hold difficult and dirty low-status jobs for little pay. Locals provide an authentic Polynesian flavor for guests, a ready pool of youthful high-turnover employees, and a population trapped in a place that offers few occupational alternatives. Managers tend to be middle-class, college-educated young and middle-aged men from the mainland whose lifestyles are occupationally transient. Seekers, mostly young, white, and from the mainland as well, escape to paradise seeking adventure, warmth, extreme sports, or some alternate life experiences.The Adlers describe the work, lives, and careers of these four groups that labor in organizations that never close, with shifts scheduled around the clock and around the year. Paradise Laborers adds to the growing interest in the global flow of labor, as these immigrant workers display different trends in gendered opportunities and mobility than those exhibited by other groups. The authors propose a political economy of tourist labor in which they compare the different expectations and rewards of organizations, employees, and local labor markets